Molecular analysis of inhibin A and activin A subunit gene loci in epithelial ovarian cancer. Issue 5 (1st August 2002) - Depasquale, S.; Lambert-Messerlian, G.; Quddus, M. R.; Campbell, I.; Steinhoff, M.; Gajewski, W.; Granai, C.; Tantravahi, U.
Abstract : Inhibin A (α-βA) and activin A (βA-βA) are biochemically similar proteins that generally have opposite biologic functions. For example, while inhibin (α subunit) is proposed to be a tumor suppressor in some types of ovarian cancer, activin appears to stimulate tumor development. Previous reports suggest that a loss of α inhibin subunit expression and elevated serum activin levels are associated with human epithelial ovarian cancer (EOC). Our objective was to examine the α inhibin subunit gene locus on chromosome 2q for evidence of loss of heterozygosity (LOH) in cases of EOC and to correlate these results with serum activin A levels measured in the same patients. Ovarian tumor and matched healthy tissue samples were collected from 22 women with EOC. DNA was extracted and subjected to PCR analysis using 10 primers, seven from chromosome 2q (α inhibin subunit locus) and, as a control, three from chromosome 7p (inhibin/activin βA subunit). In addition, each patient had a preoperative serum activin A measurement using an ELISA assay. One (1/22) case of EOC demonstrated LOH for one microsatellite marker at the α inhibin gene locus. Thirty-six percent (8/22) of patients had an activin A level that was increased above the normal range. We conclude that loss of heterozygosity at the inhibin/activin α subunit locus is not frequently associated with EOC. More direct molecular analyses of the inhibin and activin genes are warranted to rule out mutations in cases of epithelial ovarian cancer.